2014
DOI: 10.1002/jmri.24611
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of glutamine and GABA levels in patients with idiopathic generalized epilepsy using MEGAPRESS

Abstract: Purpose Idiopathic generalized epilepsies (IGE) comprise a group of clinical syndromes associated with spike wave discharges, putatively linked to alterations in neurotransmission. The purpose of this study was to investigate whether patients with IGE have altered glutamine and γ-aminobutyric acid (GABA) levels indicative of altered excitatory and inhibitory neurotransmission in frontal regions. Materials and Methods Single-voxel MEGA-edited PRESS magnetic resonance imaging (MRI) spectra were acquired from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…A recent case report documented a 5-year old male with a cystic lesion compressing the left hippocampus and exhibiting teeth grinding behavior during sleep (77). It has been found that DLPFC of idiopathic generalized epilepsy patients demonstrate increased levels of glutamine and GABA compared with controls (57). This differs from our study in that DLPFC of OCS subjects showed significantly lower levels of GABA+ and higher levels of Glu (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent case report documented a 5-year old male with a cystic lesion compressing the left hippocampus and exhibiting teeth grinding behavior during sleep (77). It has been found that DLPFC of idiopathic generalized epilepsy patients demonstrate increased levels of glutamine and GABA compared with controls (57). This differs from our study in that DLPFC of OCS subjects showed significantly lower levels of GABA+ and higher levels of Glu (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Both single voxel short echo time Point RESolved Spectroscopy (PRESS) spectra (TE=30 ms, TR=1500 ms, 128 averages) and GABA-edited spectra (TR=1500 ms, TE=68 ms) using MEGA-PRESS (55-57) were obtained from four volumes of interest (VOIs): thalamus (25×25×25 mm 3 , 392 averages), hippocampus (17×40×17 mm 3 , 512 averages), DLPFC (25×30×22 mm 3 , 392 averages) and dACC/preSMA (25×35×25 mm 3 , 392 averages). A reference spectrum without water suppression was obtained in each brain region for phase and frequency correction.…”
Section: Methodsmentioning
confidence: 99%
“…Glutamine levels have been suggested as a marker for synaptically active glutamate and excitatory neurotransmission (Chowdhury et al, 2015;Hancu and Port, 2011). Changes in glutamine levels may be a particularly sensitive measure for detecting acute downstream effects following ketamine administration.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the tight spectral overlap between Glu and Gln at 3 T, 39,41 the sum of both, Glx, was used to investigate the link between Glu levels, spindle rhythms, and schizotypy. The concentrations were corrected for partial volume contamination of CSF, 42 using the correction factor given in Chowdhury et al 43 To control for differences in the fractions of GM and WM within the voxel we covaried in an additional analysis for the GM/WM fraction 43,44 in a partial correlation design.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%